E-031 Versatile Fill Coils: Initial Experience as Framing coil for Oblong Aneurysms. (14th July 2013) - Osanai, T; Bain, M; Hui, F
Abstract : Introduction: Oblong aneurysms, with dimensions of 2:1 or greater aspect ratios, are typically coiled with framing coils with helix diameter of aneurysm (l+w)/2, thus a 6 x 3 mm aneurysm might be framed with a 4–5 mm coil. The introduction of the versatile fill coil which has two separate coil elements - loops and longer wave segments - allows another approach to framing oblong or snow-man shaped aneurysms. Methods: The endovascular database at a single institution was reviewed to assess aneurysms coiled with versatile fill coils as a framing coil yielding 3 consecutive patients in non-spherical, oblong aneurysms. The results were reviewed and demographic and outcome information collected and summarised. Results: 3 patients (1 man and 2 women) were treated with VFC coils, 1 with balloon assistance and 0 with stent assistance. All cases were diagnosis as ruptured aneurysm which located in Anterior communicate artery. There were no complications immediately post procedurally, with 1 case of intraprocedural catheter induced vasospasm which resolved with calcium channel blockers. Complete occlusion was achieved in all cases. There were no recurrent and re-bleeding during follow up periods. Conclusion: The VFC coil may offer an alternative to spherical framing coils in oblong aneurysms, as the coil structure offers elements that conform to the short axis diameter of the aneurysms, with wave elements that displace the loop elements, peripheralising along the aneurysm length. Further experience would be necessary to confirm these clinical impressions. Disclosures: T. Osanai: None. M. Bain: None. F. Hui: 2; C; Microvention.